INFLUENCE OF NON-DEMOGRAPHIC FACTORS ON INDONESIAN CONSUMERS PURCHASE INTENTION TOWARDS GREEN PRODUCTS - Hutahaean, Cynthia Irene; Kurnia, Pepey Riawati (ASEAN Marketing Journal, 2021)
This research analyzed the influence of non-demographic factors to Indonesian consumers’ attitude towards green products. Furthermore, this research also investigated the relationship between consumers’ attitude and the intention to purchase green products. This research used questionnaire data from 350 respondents selected by judgemental sampling. Data was analyzed using regression method. The research found that only five out of six non-demographic factors tested were proven to influence the Indonesian consumers’ attitude towards green products. Based on their magnitude of influence, the five factors are altruism, perceived consumer effectiveness, collectivism, perceived benefit, and environmental knowledge. Meanwhile, the interpersonal influence, another factor tested, was not proven to affect the consumers’ attitude towards green products. Consumers’ attitude towards green products also influence consumers’ intention to purchase those products.